Book Bans in the U.S.: Attempts to censor library materials as a warning sign of antidemocratic movements - Stroshane, Eric (API Magazin, 2025)
Starting in 2021, book censorship attempts in the United States increased dramatically. While not initially apparent, these censorship attempts were part of a broad antidemocratic movement driven by extremist organizations with political ties. As the rhetoric and tactics utilized by U.S. groups spreads internationally, monitoring efforts to censor library materials can provide warning of a political shift towards authoritarian rule.